Komunikasi Dialektis Masyarakat Beda Agama di Bojonegoro - Fahrudin, Nanang; Hastjarjo, Sri; Satyawan, Agung (Jurnal Komunikasi Islam, 2018)
This study discusses the manner in which villagers of "Kampung Kristen" Leran Village, Bojonegoro decide how to interact within religious heterogeneous society in order to construct social harmony. Using ethnographic of communication approach, the findings have revealed that within social communication of Leran villagers, they always face dynamic interplay between integration and separation, stability and change, expression and nonexpression. Hence, they decide to have a cautious attitude towards verbalizing ideas and emotions in words, particularly related to religious issues. In general, they prefer and are more concerned with preserving social harmony than arguing their religious beliefs.